2011
DOI: 10.1590/s1806-66902011000100030
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação agroeconômica das culturas da beterraba e coentro em função da época de estabelecimento do consórcio

Abstract: Resumo -A consorciação de culturas é uma prática de cultivo usada na produção de hortaliças, e que influencia sobremaneira a produtividade dessas culturas, além de gerar vários benefícios agroeconômicos. O objetivo do presente trabalho foi avaliar os rendimentos de beterraba (Beta vulgarias L.) e coentro (Coriandrum sativum L.) em função da época de estabelecimento do consórcio entre essas culturas. O trabalho foi conduzido na Universidade Federal Rural do Semiárido, Mossoró-RN, durante o período de julho a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
9

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
0
5
1
9
Order By: Relevance
“…Our results differ from those obtained by Grangeiro et al (2011), who found no difference in fresh mass yields of coriander between monocropping and intercropping with beet.…”
Section: Coriander Cropcontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results differ from those obtained by Grangeiro et al (2011), who found no difference in fresh mass yields of coriander between monocropping and intercropping with beet.…”
Section: Coriander Cropcontrasting
confidence: 99%
“…This explains the complementarity between different cultures, resulting in higher yields through companion cropping (GRANGEIRO et al, 2011).…”
Section: Carrot Cropmentioning
confidence: 99%
“…A significant difference was registered only between the coriander cultivars in the intercropping in the arugula green mass yield, with the -Português‖ coriander cultivar presenting the highest yield of 3.05 t ha -1 , standing out from -Verdão.‖ This behavior is probably due to the different plant species that were intercropped, with complementarity between them to make better use of available resources, conferring on them the condition of companion plants ( GRANGEIRO et al, 2011). Table 4.…”
Section: Arugula Cropmentioning
confidence: 99%
“…In the present study, significant differences were observed in the total and commercial s among the spatial arrangements with the highest values in the 2:2 arrangement (Table 1). This might be attributed to the low interspecific competition between beet and cowpea (Zanine and Santos, 2004), which allows both the crops to utilize the available resources more effectively (Grangeiro et al, 2011). Therefore, less competition and better soil utilization are expected in an intercropping system composed of plant species with roots that exploit the soil at different depths (Teixeira et al, 2005).…”
Section: Effects Of Treatments On the Agronomic Performance Of Beetmentioning
confidence: 99%